Pneumopericardium as a non-small-cell lung carcinoma complication - Kubisa, Anna; Lesińska, Anna; Dec, Paweł; Szewczak-Głodek, Małgorzata; Kochanowski, Leszek; Kubisa, Bartosz; Feledyk, Grzegorz; Czarnecka, Michalina; Wójcik, Janusz; Grodzki, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Below we present a case of a young man with symptoms of progressive weakness, fever, cough, rapid decrease in body weight and the presence of a tumor in the left axillary region. The chest radiography and echocardiography revealed gas bubbles in the pericardium. The more detailed diagnostics and computed tomography of the chest showed an infiltration of the left lung cavity and a fistula among the bronchus, pleural and pericardial cavities. Further diagnostics demonstrated that the pneumopericardium (diagnosed by means of chest radiograph and echocardiography) was a complication of a primary non-small-cell lung carcinoma.